Valuing Interest Payment Guarantees on Developing Country Debt. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper develops a technique to value guarantees on interest payments on developing-country debt, and provides some preliminary estimates of the cost of such guarantees. The cost of interest payment guarantees is not directly observable because a guarantee is a contingent obligation that becomes effective only if the debtor fails to make a certain payment. The strategy adopted in this paper is to estimate the market price that an interest payment guarantee would have if such a contract existed and were traded in financial markets. Using results from option pricing theory it is possible to calculate the price that an 'interest guarantee contract' would carry in financial markets on the basis of the price of developing-country debt in secondary markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States